2015
DOI: 10.1186/s12885-015-1208-y
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation and histone modifications regulate SOX11 expression in lymphoid and solid cancer cells

Abstract: BackgroundThe neural transcription factor SOX11 is present at specific stages during embryo development with a very restricted expression in adult tissue, indicating precise regulation of transcription. SOX11 is strongly up-regulated in some malignancies and have a functional role in tumorgenesis. With the aim to explore differences in epigenetic regulation of SOX11 expression in normal versus neoplastic cells, we investigated methylation and histone modifications related to the SOX11 promoter and the possibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 56 publications
0
17
0
3
Order By: Relevance
“…One possibility is that SOX11 is methylated in normal adult mammary cells, and becomes hypomethylated in cancer, particularly Her2-positive and basal-like breast cancers. Hypomethylation of oncogenic genes has been associated with many cancer types [ 14 ]; and methylation has been shown to be associated with SOX11 expression in hematopoietic and solid tumors [ 15 , 16 ]. Therefore, we investigated methylation of CpG sites near the SOX11 genomic location.…”
Section: Resultsmentioning
confidence: 99%
“…One possibility is that SOX11 is methylated in normal adult mammary cells, and becomes hypomethylated in cancer, particularly Her2-positive and basal-like breast cancers. Hypomethylation of oncogenic genes has been associated with many cancer types [ 14 ]; and methylation has been shown to be associated with SOX11 expression in hematopoietic and solid tumors [ 15 , 16 ]. Therefore, we investigated methylation of CpG sites near the SOX11 genomic location.…”
Section: Resultsmentioning
confidence: 99%
“…DNA methylation is an important type of epigenetic modification, and has been reported to be involved in tumorigenesis. Previous studies have identified that DNA methylation changes may result in aberrant gene expression in cancer (16,17), and a number of them may be an early molecular marker (18,19). focus of the present study was on the silencing of linc00086 by DNA methylation in GC.…”
Section: Discussionmentioning
confidence: 94%
“…Trichostatin A (TSA) and vorinostat (SAHA) are commonly used as histone deacetylase inhibitors, and increased expression of SOX11 can be observed in breast cancer, neuroblastoma, Burkitt lymphoma, and MCL by TSA and SAHA treatment via the inhibition of histone deacetylation. 14,66 Furthermore, the treatment of 5-aza-2’-deoxycytidine, a DNA methyltransferase inhibitor, can upregulate expression of SOX11 in the NPC cell line CNE2 and consequently inhibit growth and invasion of NPC. 17 Although the epigenetic regulation of SOX11 in cancer is complicated, the application of epigenetic agents targeting SOX11 may provide new options for cancer therapy, which urgently need further investigation.…”
Section: Clinical Relevance Of Sox11 In Carcinomamentioning
confidence: 99%